The Influence of Customer Satisfaction on Service Quality at Bank Syariah Indonesia KCP Medan Simpang Limun - Annisa Zuhra; Imsar Imsar; Tuti Anggraini (Universitas Islam Negeri Sultan Maulana Hasanuddin Banten, 2025)
This study aims to analyze the level of customer satisfaction regarding service quality at Bank Syariah Indonesia KCP Medan Simpang Limun using the Customer Satisfaction Index (CSI) approach. The method employed is quantitative research with a descriptive approach, involving 95 respondents selected through purposive sampling. The results show a significant effect between customer satisfaction and the quality of service provided. The simultaneous test (F-test) yielded a significance value of 0.000, which is less than 0.05, indicating that changes in customer satisfaction simultaneously affect service quality. The partial test (T-test) also supports this finding, where the calculated T value for the customer satisfaction variable is 11.201, much greater than the specified T table value of 1.985 with a significance level of 0.000. This study also results in a Customer Satisfaction Index (CSI) of 89.54%, which falls into the very satisfied category (81% - 100%). Thus, it can be concluded that Bank Syariah Indonesia KCP Medan Simpang Limun has successfully met customer expectations in terms of service quality, indicating that customer satisfaction is an important element that needs to be maintained and improved through continuous enhancement.